SUFISM IN THE PERSPECTIVE OF ABDUL QADIR AL-JAILANI - N, Syukron; Nurhuda, Abid; Nisa N, Khoirun (Universitas Islam Syekh-Yusuf, 2023)
Sufism is often seen as a factor that hinders the progress of Muslims and is identified with the figure of someone lazy, stupid, poor, and backward. Even though it has a solid foundation and is sourced from the Qur'an and hadith. It has existed since the time of the Prophet Muhammad until later times, while one of the popular figures known at his time until now is Abdul Qadir al-Jailani. So the purpose of this study is to describe Sufism in the Perspective of Abdul Qadir Al-Jailani. The method used is a literature study by collecting primary and secondary data sources. Then analyzed the contents and the last is concluded. The results of the study indicate that Sufism in the Perspective of Abdul Qadir Al-Jailani includes repentance, shafa', territory, and mortal' following the book Sirr Al-Asrar Wa Madhhar AlAnwar. Whereas the book al-Ghunyah Li Talib Tariq al-Haq includes repentance, resignation, akhlakul karimah, gratitude, sabra, ridho, and Siddiq. All of the above shows a practical emphasis on tazkiyatun nafs through the process of mujahadah.